The Influence of Personal Selling, Product Knowledge, and Customer Relationship Management (CRM) on Purchasing Decisions at Optics Nice Sidoarjo - Shafa Safhira Irawansyah; Rusdi Hidayat Nugroho (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine and analyze the effect of Personal Selling, Product Knowledge, and Customer Relationship Management (CRM) variables on purchasing decisions at Optik Nice Sidoarjo with a total of 100 respondents who are Optik Nice Sidoarjo customers. Data was collected by distributing questionnaires that had been tested for validity and reliability to ensure data accuracy and consistency. Data analysis was performed using SmartPLS software version 4.0. This study tests the hypothesis using the Structural Equation Model (SEM) with the Partial Least Square (PLS) analysis method. The measurement scale in this study uses a Likert scale. The results showed that personal selling and customer relationship management had a significant positive effect on purchasing decisions. Meanwhile, the product knowledge variable produces an insignificant effect on purchasing decisions at Optik Nice Sidoarjo. These findings indicate that emotional closeness and effective communication are more influential than product knowledge. Therefore, companies are advised to focus on improving the quality of employee service.